Property Rights, Risk, & Livestock Development in Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Proceedings of an international symposium, held in Germany, in September 1998.Edited by N McCarthy, B Swallow et al. ILRI & IFPRI. 2000. 433pp.ISBN 0 89629 339 6IFPRI2033 K Street NW, Washington, DC 20006-1002, USAFax: +1 202 467 44 39Email:...